1997
DOI: 10.1007/s11627-997-0053-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro clonal propagation of an aromatic medicinal herb Ocimum basilicum L. (sweet basil) by axillary shoot proliferation

Abstract: An efficient protocol for in vitro propagation of an aromatic and medicinal herb Ocimum basilicum L. (sweet basil) through axillary shoot proliferation from nodal explants, collected from field-grown plants, is described. High frequency bud break and maximum number of axillary shoot formation was induced in the nodal explants on Murashige and Skoog (1962) medium (MS) containing N6-benzyladenine (BA). The nodal explants required the presence of BA at a higher concentration (1.0 mg' [ -t, 4.4 ttM) at the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
44
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 11 publications
13
44
1
Order By: Relevance
“…For the induction of strong and stout root systems the elongated shoots were individually cultured on half strength MS medium with 1.0 mg/l IBA which gave the best response with 91.60 % of roots produced and on an average of 22.83 roots per shoot were recorded within 4 weeks. The effectiveness of IBA in rooting has been reported for many medicinal plants, viz; Aegle marmelos (Puhan and Rath 2012), Alpinia zerumbet (Rakkimuthu et al 2011), Clitoria ternatea L. (Barik et al 2007), Murraya koenigii (L.) Spreng (Bhuyan et al 1997) and Ocimum basilicum L. (Sahoo et al 1997). This is due to an imbalance between endogenous auxin and exogenously supplied auxin IBA (Manickam et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For the induction of strong and stout root systems the elongated shoots were individually cultured on half strength MS medium with 1.0 mg/l IBA which gave the best response with 91.60 % of roots produced and on an average of 22.83 roots per shoot were recorded within 4 weeks. The effectiveness of IBA in rooting has been reported for many medicinal plants, viz; Aegle marmelos (Puhan and Rath 2012), Alpinia zerumbet (Rakkimuthu et al 2011), Clitoria ternatea L. (Barik et al 2007), Murraya koenigii (L.) Spreng (Bhuyan et al 1997) and Ocimum basilicum L. (Sahoo et al 1997). This is due to an imbalance between endogenous auxin and exogenously supplied auxin IBA (Manickam et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to Liu et al (2000) IBA was shown to promote more and stronger root formation in Salvia sclarea than IAA. Sahoo et al (1997) also reported that, of the three auxins tested (IBA, IAA, and NAA) with Ocimum basilicum, IBA was most effective in inducing rooting and obtaining the highest number and length of roots. For root initiation, IAA was reported as the least successful auxin in Salvia valentine (Cuenca and Amo-Marco, 2000).…”
Section: Discussionmentioning
confidence: 92%
“…The highest average root number (5,4±1,2) was established on the medium with 0.7 mg.ml -1 IBA. It has been reported that in Ocimum basilicum, IBA stimulated root formation and increased dramatically number and length of roots (9). According to Liu et al (10), IBA was shown to promote stronger root formation in Salvia sclarea than IAA.…”
Section: Resultsmentioning
confidence: 98%